Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

De l'usage épistémologique et politique des catégories de « sexe » et de « race » dans les études sur le genre - Dorlin, Elsa (Cahiers du Genre, 2005)
À partir d’une réflexion sur le black feminism , cet article traite de l’articulation entre domination de genre et racisme, en tant qu’elle constitue l’un des enjeux théoriques et politiques les plus importants du féminisme anglo-saxon : dans quelle mesure l’expérience de la ségrégation raciste modèle celle du sexisme et met à mal l’unité politique du féminisme ? Si le sujet idéologique « femme » a implosé sous la critique du patriarcat, qu’en est-il du sujet politique du féminisme lui-même, « Nous les femmes » ? Notre thèse consiste à montrer comment les discours de la domination mettent à disposition des groupes opprimés des cadres anhistoriques qui réifient sans cesse ces mêmes groupes, jusque dans leurs affirmations positives. Dans ces conditions, en voulant déessentialiser le sujet du féminisme, « les femmes », le risque est de le renaturaliser en une myriade de sous-catégories (les femmes noires, les femmes voilées, les femmes migrantes...) qui deviennent des préalables aux luttes. De notre capacité à révéler l’historicité de l’entremêlement des catégories de « sexe » et de « race » et à user de techniques de tumultes à même d’inventer un autre langage politique, dépend notre capacité d’agir et de se penser comme sujets politiques en devenir.
Keywords: afro-féminisme; approches et analyses; cours; cycles supérieurs; discipline; fem9000; féminismes noirs; har4610; histoire et politique; intersectionnalité; patriarcat; racisme; ressource en ligne; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; épistémologie